Effects of C-xylopyranoside derivative on epithelial regeneration in an in vitro 3D oral mucosa model. Issue 7 (2nd July 2016) - Uenoyama, Atsushi; Kakizaki, Ikuko; Shiomi, Aki; Saito, Naoaki; Hara, Yuko; Saito, Taro; Ohnuki, Hisashi; Kato, Hiroko; Takagi, Ritsuo; Maeda, Takeyasu; Izumi, Kenji
Abstract: Identifying substandard tissue-engineered oral mucosa grafts with a poor epithelium before clinical use is critical to ensure quality assurance/control in regenerative medicine, leading to success of grafting. This study investigated the effects of one of the C-xylopyranoside derivatives, β-D-xylopyranoside-n-propane-2-one (XPP), on oral epithelial regeneration. Using a three-dimensional oral mucosa model, we analyzed changes of the epithelial structure, glycosaminoglycan (GAG) synthesis, the expression levels of basement membrane zone markers, and substrates of Akt/mTOR signaling. Compared with the control, 2 mM XPP treatment increased the mean and minimal epithelial thickness, and reduced the variation of epithelial thickness. It also stimulated expressions of decorin and syndecan-1 with change of GAG amount and/or composition, and enhanced the expressions of integrin α6, CD44, and Akt/mTOR signaling substrates. These findings suggest that XPP supplementation contributes to consistent epithelial regeneration. Moreover, upregulation of those markers may play a role in increasing the quality of the oral mucosal epithelium. Graphical abstract: : XPP had an effect on consistent epithelial regeneration in an in vitro 3D oral mucosa model (A: Histologic examination, B: Histomorphometric analysis).